America's Ethan Allen - Holbrook, Stewart H., 1893-1964.; Ward, Lynd, 1905-1985 (Boston, Houghton Mifflin Co., 1949)
A biography of the patriot and soldier who led the Green Mountain Boys in the capture of Fort Ticonderoga from the British in 1775.
Keywords: Allen, Ethan, -- 1738-1789 -- Juvenile literature; Allen, Ethan, -- 1738-1789.; Revolutionaries -- United States -- Biography -- Juvenile literature; Soldiers -- United States -- Biography -- Juvenile literature; United States -- History -- Revolution, 1775-1783 -- Juvenile literature; Vermont -- History -- Revolution, 1775-1783 -- Juvenile literature; United States -- History -- Revolution, 1775-1783 -- Biography